The constitutionalism of American states - Connor, George E., 1959-; Hammons, Christopher W. (Eric Voegelin Institute series in political philosophy., 2008)
"This comparative study of state constitutions offers insightful overviews of the general and specific problems that have confronted America's constitution writers since the country's founding. Each chapter reflects the constitutional theory and history of a single state, encompassing each document's structure, content, and evolution"--Provided by publisher.